The Effectiveness of Reproductive Health Education on Increasing Adolescents' Knowledge and Behavior Regarding Premarital Sex Among Female Students of State Senior High School 1 Tarumajaya in 2025 - Tatag Mulyato; Eka Novia Noor Safitri; Safira Putri; Eko Wahyudiono (Universitas Pahlawan Tuanku Tambusai, 2026)
Adolescence is a transitional period that is vulnerable to reproductive health issues, including premarital sexual behavior, due to a lack of knowledge. This study aims to determine the effectiveness of reproductive health education on premarital sexual knowledge and behavior in 50 11th grade female students of SMA Negeri 1 Tarumajaya in 2025, using a quantitative pre-experimental method with a one-group pretest-posttest design and video media intervention. The results showed a significant increase in female students' knowledge and behavior after education, thus proving effective in shaping responsible adolescent behavior. It is recommended that schools collaborate with health workers to implement ongoing reproductive health education programs as an effort to prevent risky sexual behavior.